COMMUNITY EDUCATION RELATED TO THE USE OF FAMILY MEDICINE PLANTS IN VILLAGE GIRIAWAS, GARUT DISTRICT, JAWA BARAT - Framesti Frisma Sriarumtias (Indonesian Journal of Community Empowerment (IJCE), 2020)
Community service this time aims to motivate the community to utilize the house yard into land for family medicinal plants (TOGA). The method used is in the form of counseling and data collection on plants that are usually planted by residents. Counseling is done by lecturing by distributing reading material in the form of material handouts delivered. And data collection is done by discussing with the people who attended the event. The target of this service is the women of recitation in Giri Ayu Village, Giriawas Village, Garut Regency, West Java. The results of this community service are able to understand related to the utilization of family medicinal plants that can be used for prevention.